Effects of regular away travel on training loads, recovery, and injury rates in professional Australian soccer players - Fowler, P.; Duffield, R.; Waterson, A.; Vaile, J. (International Journal of Sports Physiology and Performance, 2015)
The current study examined the acute and longitudinal effects of regular away travel on training load (TL), player wellness, and injury surrounding competitive football (soccer) matches. Eighteen male professional football players, representing a team competing in the highest national competition in Australia, volunteered to participate in the study. Training loads, player wellness and injury incidence, rate, severity, and type, together with the activity at the time of injury, were recorded on the day before, the day of, and for 4 d after each of the 27 matches of the 2012-13 season. This included 14 home and 13 away matches, further subdivided based on the midpoint of the season into early (1-13) and late competition (14-27) phases. While TLs were significantly greater on day 3 at home compared with away during the early competition phase (P = .03), no other significant effects of match location were identified (P > .05). Total TL and mean wellness over the 6 d surrounding matches and TL on day 3 were significantly reduced during the late compared with the early competition phase at home and away (P < .05). Although not significantly (P > .05), training missed due to injury was 60% and 50% greater during the late than during the early competition phase at home and away, respectively. In conclusion, no significant interactions between match location and competition phase were evident during the late competition phase, which suggests that away travel had negligible cumulative effects on the reduction in player wellness in the latter half of the season.